2017
DOI: 10.1242/jcs.196881
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin intermediate filaments control actin stress fiber assembly through GEF-H1 and RhoA

Abstract: The actin and intermediate filament cytoskeletons contribute to numerous cellular processes, including morphogenesis, cytokinesis and migration. These two cytoskeletal systems associate with each other, but the underlying mechanisms of this interaction are incompletely understood. Here, we show that inactivation of vimentin leads to increased actin stress fiber assembly and contractility, and consequent elevation of myosin light chain phosphorylation and stabilization of tropomyosin-4.2 (see Geeves et al., 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
170
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 168 publications
(191 citation statements)
references
References 63 publications
17
170
4
Order By: Relevance
“…14 Moreover, vimentin interacts with the RAF-1/RhoA signaling pathway 15,16 to mediate actin dynamics and focal adhesion formation, 17 and vimentin depletion resulted in increased myosin light chain phosphorylation (MLC 20 ) and increased contractility in human osteosarcoma and human dermal fibroblasts. 18 Previous studies have demonstrated that JNK along with its substrate c-Jun is activated in response to mechanical stretch in rodent and human BSM cells. [19][20][21] In the current study, we transduced IF proteins into murine BSM strips via an adenovirus to examine the sufficiency of increased IF protein expression to reduce BSM contraction.…”
Section: Introductionmentioning
confidence: 98%
“…14 Moreover, vimentin interacts with the RAF-1/RhoA signaling pathway 15,16 to mediate actin dynamics and focal adhesion formation, 17 and vimentin depletion resulted in increased myosin light chain phosphorylation (MLC 20 ) and increased contractility in human osteosarcoma and human dermal fibroblasts. 18 Previous studies have demonstrated that JNK along with its substrate c-Jun is activated in response to mechanical stretch in rodent and human BSM cells. [19][20][21] In the current study, we transduced IF proteins into murine BSM strips via an adenovirus to examine the sufficiency of increased IF protein expression to reduce BSM contraction.…”
Section: Introductionmentioning
confidence: 98%
“…Oligonucleotides for cloning guide RNA into pSpCas9 (BB)-2A-GFP vector (a gift from Feng Zhang, Addgene # 48138) were designed as described previously [42]. Forward primer: 5’ CACCG CTCATCACGCCTCGCCCTGT 3’ and reverse primer: 5’ AAAC ACAGGGCGAGGCGTGATGAG C 3’ (guide sequence underlined) for targeting exon 1.…”
Section: Star Methodsmentioning
confidence: 99%
“…The numbers and width of actin filaments bundles from cells plated on crossbow micro-patterns were analysed by the FilamentSensor software as described before [32]. The numbers of thin arcs and thick arcs were manually counted from leading edge of the cells plated on micro-pattern as previously described [42]. The manual quantification in this assay, as well as in the one presented in Figure 5 for the number of myosin II stacks, was blinded in the way that the person analysing the images was provided a randomized set of images for quantification.…”
Section: Star Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro studies that used green fluorescent protein (GFP)tagged vimentin (Jiu, 2017) and immunofluorescence studies of fixed cells (Prahlad, Yoon, Moir, Vale, & Goldman, 1998;) demonstrated that vimentin exists in cells as fragments of different lengths: short filaments (squiggles), long mature filaments, and nonfilamentous particles. Short ULF fragments with the average size of 130 nm were mainly localized close to small cell-matrix adhesions, while long IFs were found in the proximity of large focal adhesions (Terriac et al, 2017).…”
Section: Introductionmentioning
confidence: 99%